SEXUAL EDUCATION IN SCHOOLS: NEEDS, CHALLENGES AND STRATEGIES - Iwan Ridwan; Nurul Lail Rosyidatul Mu'ammaroh; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
Sexual education in schools is a critical necessity to ensure students' reproductive wellbeing and health. The implementation of sexual education faces various challenges, including social and cultural stigma, lack of training for educators, and limited policy support. However, the importance of this topic drives the need for comprehensive strategies, such as inclusive curriculum development, intensive training for teachers, parental involvement, and policy support from the government. These strategies aim to overcome these barriers and increase the effectiveness of sexual education in schools, positively impacting the younger generation